PENGARUH TANGGUNG JAWAB SOSIAL DAN TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VAIRABEL MEDIASI - Mohammad Fadhly Azzuhry; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2023)
The writing of this scientific paper aims to examine the Effect of Corporate Social Responsibility and Corporate Governance on Financial Performance with Earnings Management as a Mediating Variable listed on the Indonesia Stock Exchange (IDX) in 2021. 140 samples of manufacturing companies were used in this study. The GRI Standard Index is used in this study to measure the corporate social responsibility index. Corporate governance mechanisms are reflected through the proportion of independent commissioners, constitutional ownership, and audit quality. For earnings management, using a Jones (1991) model developed by Dechow et al. (1995) for the measurement of discretionary accruals. The company's financial performance is reflected through Earnings per Shares (EPS), Return on Assets (RoA), and TOBIN's Q. This research uses Partial Least Squares-SEM (PLS-SEM) for data analysis methods..The findings of this study are corporate social responsibility has a positive and significant effect on the company's financial performance. Corporate social responsibility has no significant effect on earnings management. Earnings management as a mediating variable in this study does not have a significant relationship with financial performance, and cannot mediate the effect of corporate social responsibility on the company's financial performance. Corporate governance in this study cannot affect the company's financial performance, and earnings management cannot mediate the effect of the relationship between corporate governance and the company's financial performance.